Road Accident due to a Pancreatic Insulinoma. Issue 12 (March 2015) - Parisi, Amilcare; Desiderio, Jacopo; Cirocchi, Roberto; Grassi, Veronica; Trastulli, Stefano; Barberini, Francesco; Corsi, Alessia; Cacurri, Alban; Renzi, Claudio; Anastasio, Fabio; Battista, Francesca; Pucci, Giacomo; et al.
<x xml:space="preserve">Abstract</x> Abstract Insulinoma is a rare pancreatic endocrine tumor, typically sporadic and solitary. Although the Whipple triad, consisting of hypoglycemia, neuroglycopenic symptoms, and symptoms relief with glucose administration, is often present, the diagnosis may be challenging when symptoms are less typical. We report a case of road accident due to an episode of loss of consciousness in a patient with pancreatic insulinoma. In the previous months, the patient had occasionally reported nonspecific symptoms. During hospitalization, endocrine examinations were compatible with an insulin-producing tumor. Abdominal computerized tomography and magnetic resonance imaging allowed us to identify and localize the tumor. The patient underwent a robotic distal pancreatectomy with partial omentectomy and splenectomy. Insulin-producing tumors may go undetected for a long period due to nonspecific clinical symptoms, and may cause episodes of loss of consciousness with potentially lethal consequences. Robot-assisted procedures can be performed with the same techniques of the traditional surgery, reducing surgical trauma, intraoperative blood loss, and hospital stays.